Improving composting as a post-treatment of anaerobic digestate. (February 2016) - Zeng, Yang; De Guardia, Amaury; Dabert, Patrick
Highlights: Practical parameters were studied to improve composting as a post-treatment of anaerobic digestate. The use of "active" bulking agent like dry wood chips serving as water and nitrogen sinks was indispensable. The recycling of compost reduced ammonia emission but stimulated nitrous oxide emission. The increase of self-heating potential of composting pile could be successfully achieved by moderating the aeration rate. The regulation of practical parameters could effectively ameliorate the performance of composting of digestate. Abstract: This work investigated the influences of practical parameters upon composting of digestate. The yardsticks for evaluation were digestate stabilization, nitrogenous emissions mitigation and self-heating potential. The results suggest choosing an "active" bulking agent like dry wood chips (WC) which served as free-water and nitrogen sink through composting. At an optimal volumetric WC:digestate mixing ratio of 4:1, nearly 90% of the initial NH4 + /NH3 were fixed, which reduced significantly nitrogenous emissions. This mixing ratio also improved the stabilization and self-heating potential. Using small particle size WC increased narrowly O2 consumption and reduced NH3 emission. Storing used WC prior to recycling reduced 40% N2 O emission compared to directly recycled WC. Recycling compost helped to decrease NH3 emission, but quadrupled N2 O emission. The optimal aeration rate (15 L h −1 kg OM0 ) which was lower compared to composting of organic waste, was enough to ensure the O2 supply and ameliorate the self-heating potential through composting of digestate.